Caja Real de Lima: registro contable del oro fiscal, siglos XVI-XIX - Luque Luque, Juvenal (2008)
This work discusses one of scarcely studied aspects of fiscality in colonial Peru. More especifically, this work deals with the analysis of account books of the Royal Treasure and the ways incomes releated to Quinto Real were registered from the sixteenth through the nineteenth centuries. To accomplish this objective, I have analyzed several books of the Royal Treasure of Lima. In this opportunity, my goal is only to present the intricate forms of account registration but not to make a periodization, due to the difficulties this task implies at the present level of my research. An innovative aspect of this essay is the study and quantification of gold production in the said period through the analysis of the Quinto Real information and, when this will be impossible, the summaries provides by Herbert S. Klein and John J. TePaske. Since the majority of miners paid the Quinto Real in reales, this work takes this circumstance into account to unify the information provided both by Klein-TePaske and that I have found in the books in Peruvian Archives.